[TI Collection of articles, letters, and broadcasts regarding cigarette tax] (Tufts Archival Research Center, 2007)
Draft; Collection of Tobacco Institute memos, articles, reports, and broadcasts regarding cigarette excise taxes. Includes summaries of news conferences, a report on how such a tax would affect Social Security recipients, and articles on the Consumer Price Index, tobacco farmers, and tobacco workers. Contains letters from CLUW and A. Philip Randolph to Congress members opposing cigarette taxes.